Pemanfaatan Media Sosial Dinas Perhubungan Surabaya dalam Perspektif Kearsipan Digital - Rio Febriannur Rachman (Idarotuna : Journal of Administrative Science, 2021)
Optimalization of information and communication technology in public services is a community need in the new media era. No doubt, the government at the central, provincial, and regional levels, is actively innovating in the aspect of strengthening the technology, including the form of social media. The Government of Surabaya City is one of the pioneers of information and communication technology based on public services. Almost all agencies make breakthroughs in the field of optimizing social media. This article discusses how the Surabaya Transportation Service, as one of the regional apparatus organizations, manages social media in order to maximize public services. This study uses the theory of technological determination and public policy as the rationale. The theories and concepts of administration, in particular, with respect to digital archives are also put forward. Descriptive qualitative method with literature review approach is used as a framework for formulating conclusions. Data collection is done through literature searches and other documents related to the topic. The analysis technique is done through reduction, presentation, and formulation of conclusions. The result of this study indicate that the social media utilization policy carried out by the Surabaya Transportation Service is running well and has a positive impact on the community. This study can add to the treasures of research in the field of public policy and digital archives in relation to the phenomenon of technological determination in the current era.